Happy Moms, Happier Dads: Gendered Caregiving and Parents' Affect. (December 2019) - McDonnell, Cadhla; Luke, Nancy; Short, Susan E.
Parenting is emotionally demanding and highly gendered. We use data from the American Time Use Survey to examine mothers' and fathers' momentary affect during childcare activities. We observe a gender imbalance in the emotional rewards of childcare: Fathers report more happiness, less stress, and less tiredness than mothers. We introduce the "care context"—defined as the type of childcare activity, when and where it takes place, who is present, and how much care is involved—as an explanation for these gender differences in parents' affect. The analysis reveals that most dimensions of the care context vary between mothers and fathers. We also find that the care context fully accounts for differences in mothers' and fathers' happiness, partially explains differences in stress, and does little to explain differences in tiredness. Thus, the gender imbalance in the emotional rewards of childcare is partially due to parents' highly gendered engagement with their children.